Prevalence of changes in maxillary sinus through digital panoramic radiographs of the Tiradentes University (Research, Society and Development, 2022)
The maxillary sinuses, an anatomical structure viewed radiographically by a wide radiolucent area in the posterior region of the maxilla and are the largest of the paranasal cavities and can be located on digital panoramic radiographs. In this area, extensions, intrasinusal septum and some pathological changes can be found. This research aims to investigate and determine the prevalence of the main types of anatomical and pathological changes in maxillary sinuses with their exact locations through digital panoramic radiographs from the image bank of the Radiology Clinic of the Tiradentes University (UNIT). The sample consisted of 878 exams, totaling 1756 maxillary sinuses. To assess the association between variables, the non-parametric Chi-square association test was used, with a level of statistical significance at p